2018
DOI: 10.5114/aoms.2018.75085
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of PDGF-BB and serum-stimulated responses in vascular smooth muscle cell proliferation by hinokitiol via up-regulation of p21 and p53

Abstract: IntroductionVascular smooth muscle cell (VSMC) proliferation plays a major role in the progression of vascular diseases. In the present study, we established the efficacy and the mechanisms of action of hinokitiol, a tropolone derivative found in Chamaecyparis taiwanensis, Cupressaceae, in relation to platelet-derived growth factor-BB (PDGF-BB) and serum-dependent VSMC proliferation.Material and methodsPrimary cultured rat VSMCs were pre-treated with hinokitiol and then stimulated by PDGF-BB (10 ng/ml) or seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…P21 is a well-known anti-proliferation gene, and PCNA and cyclin D2 are reported to exert an pro-proliferative effect in VSMCs [16,17]. Our results showed that LIPCAR markedly increased CDK2 and PCNA expression and decreased p21 expression, suggesting that LIPCAR accelerates the cell cycle by inhibiting P21 and activating CDK2 expression, thus promoting proliferation of VSMCs.…”
Section: Discussionmentioning
confidence: 52%
“…P21 is a well-known anti-proliferation gene, and PCNA and cyclin D2 are reported to exert an pro-proliferative effect in VSMCs [16,17]. Our results showed that LIPCAR markedly increased CDK2 and PCNA expression and decreased p21 expression, suggesting that LIPCAR accelerates the cell cycle by inhibiting P21 and activating CDK2 expression, thus promoting proliferation of VSMCs.…”
Section: Discussionmentioning
confidence: 52%
“…Evidence suggested that lncRNA such as CTHRC1 might regulate several signaling pathways through microRNA [27][28][29][30]. Ma et al reported that CTHRC1 facilitated the Wnt/PCP-Rho-JNK pathway by forming the Wnt-receptor complex [9].…”
Section: Discussionmentioning
confidence: 99%
“…Humphreys et al reported that miR-18a-5p regulates tumor cell cycle progression by targeting CDC42 , but whether CDC42 is involved in the VSMCs cycle control is unclear [ 31 ]. Further research is needed to determine the role of upstream regulatory proteins of the AKT/ERK signaling pathway, including phosphatidylinositol-3-hydroxykinase [ 32 ], platelet-derived growth factor B [ 33 ], and mitogen-activated protein kinase [ 34 ] in mediating the impact of miR-18a-5p on the abnormal VSMCs biological functions.…”
Section: Discussionmentioning
confidence: 99%